Analysis of Traditional Chinese Medicine Practice in Malaysia Knee Osteoarthritis Patients - Yu, Shichao; Keong Te, Kian; Pin Yap, Yau (Cuestiones de Fisioterapia, 2024)
Background: Malaysia has preserved and inherited the richness of Traditional Chinese Medicine (TCM). Knee Osteoarthritis (KOA) is common in Malaysia. Despite various TCM treatment methods in the region, research and reporting on TCM therapy for KOA are lacking. This study aims to compare TCM techniques used by practitioners in Malaysia and China for treating KOA through a questionnaire survey.Methods: The survey questionnaire focusing on TCM treatments for KOA was distributed to TCM physicians and acupuncturists in both countries by E-mail, WhatsApp, WeChat, etc. Use Excel 2019 to organize data and analysis.Result: 489 and 873 valid questionnaires from Malaysia and China were respectively gathered. Traditional acupuncture (TA) emerged as the predominant choice in both nations, with an 81.60% preference in Malaysia and 93.13% in China. Beyond TA, Malaysian TCM landscape favored Massage (78.53%), Cupping (76.28%), Moxibustion (64.21%), Bloodletting (54.60%), Electroacupuncture (EA) (48.26%), and Chinese herbs (41.31%). China leaned more toward EA (84.19%), Chinese Herbs (80.53%), Massage (72.51%), Moxibustion (68.84%), and Cupping (58.53%).Conclusion: In this survey, significant differences in KOA TCM treatment methods were found between China and Malaysia. While both countries widely use TA, Malaysia tends to favor non-invasive techniques like massage and cupping, whereas China leans toward EA and invasive methods such as intra-articular injections. Cultural and regulatory factors influence these variations, resulting in diverse TCM approaches. However, Malaysia faces the challenge of lacking unified evaluation system and standardized procedures for TCM.